(3GdEfHGA HCf GdYUG ef Sff GdCfHjGAs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi MeO ef CWGYg hPe ef YUGg CeG HYO abO SFdJ Yf eG jJYdb HGdYUG heG hQO ai MbgG eeG ETJgQ Ydi GdCdSfI Cf ef LGhR GdCQHYjf hde jCNP GdYUG abO YUi s
(3BNQgG (B:s
(3hcGfJ JVF HGddjd eKd GdSQGL hEPG XgQ dg YOh hcGfJ JMGQHg hJfGVd Yfg hNJe Gddg dfG HGdMSfi hHdZfG GdebGe GdCSfi hGddg CYde HGdeHOGA hGdefJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs